2020
DOI: 10.1097/md.0000000000020943
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced hypertension is associated with angiotensin II activity and total nitric oxide

Abstract: Angiotensin II mediates exercise-induced hypertension (EIH), which adversely impacts future cardiovascular health. There is paucity of data on the association between EIH and angiotensin II in well-trained middle-aged marathoners. Therefore, we investigated the renin-angiotensin-aldosterone-system and total nitric oxide activity in middle-aged marathoners with EIH. Seventy middle-aged marathoners were divided into 3 groups: normal blood pressure ([NBPG] [n = 21]), EIH group ([EIHG] [n = 35]), and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Vigorous or prolonged exercise activity frequently incurs the activation of pathological cardiac pathways and yields elevated biomarkers of cardiac damage [ 33 ]. Furthermore, some competitive long-distance runners developed exercise-induced hypertension, which was associated with an abnormal level of angiotensin-II [ 34 ]. ET-1 was also found elevated significantly in the Ex.…”
Section: Discussionmentioning
confidence: 99%
“…Vigorous or prolonged exercise activity frequently incurs the activation of pathological cardiac pathways and yields elevated biomarkers of cardiac damage [ 33 ]. Furthermore, some competitive long-distance runners developed exercise-induced hypertension, which was associated with an abnormal level of angiotensin-II [ 34 ]. ET-1 was also found elevated significantly in the Ex.…”
Section: Discussionmentioning
confidence: 99%
“…The modality by which vascular response to exercise training can be influenced in hypertensive individuals has been studied by the SEFRET study, while in spontaneous hypertensive mice the lack of a positive effect of high intensity exercise on endothelial function was found to be related to NO availability imbalance[ 40 , 41 ]. Kim et al [ 42 ] enrolled middle-aged marathoners with exercise-induced hypertension and reported increased angiotensin II with a reduction in NO levels. These findings may explain the deterioration of arteries vasodilator capacity and elevated blood pressure during exercise in this group of long-distance runners, as well as the therapeutic effect of angiotensin II inhibitors in patients with exercise-induced hypertension.…”
Section: Effects Of Exercise On Vascular Function and Structurementioning
confidence: 99%
“…It has been found that EIH is linked to angiotensin II and nitric oxide (NO) activities during exercise. The renin-angiotensin-aldosterone system (RAAS) changes during and after exercise treadmill test in marathon runners were observed by Chul-Hyun Kim [ 20 ]. The study reported a reduction in angiotensin II and no significant change in NO in people with normal blood pressure after exercise.…”
Section: Reviewmentioning
confidence: 99%
“…However, angiotensin II remained elevated with a reduction in NO in runners with EIH. Since the RAAS system plays a role in regulating blood pressure, these results may explain the reduction in the vasodilatory effect of arteries, leading to an increase in BP during exercise [ 20 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation